Spontaneous recovery of complete atrioventricular block complicating acute anterior wall ST elevation myocardial infarction. Issue 1 (20th November 2012) - Sasikumar, Navaneetha; Kuladhipati, Indra
Abstract : Background: Complete atrioventricular block complicating acute anterior wall ST elevation myocardial infarction (MI) is classically considered one of the worst prognostic indicators. Methods: We present the case of a gentleman who developed complete atrioventricular block during the course of acute anterior wall ST elevation MI, and had spontaneous resolution of the same. Mechanisms of spontaneous resolution of complete atrioventricular block in the setting of acute MI are discussed. Attention is drawn to a subgroup of patients, albeit a minority, who have a better prognosis owing to reversible causes than classically expected and seen. Results: Clinical features suggested that this patient had reocclusion of the infarct-related artery after thrombolysis on presentation and spontaneous reperfusion. Conclusion: Coronary angiography provides invaluable information for decision making in such clinical scenarios. Complete atrioventricular block due to reversible ischaemia produced by reocclusion of an infarct-related artery should be reversible by percutaneous coronary angioplasty of the infarct-related artery. We suggest that reversible causes be considered before attributing atrioventricular block to irreversible damage, which would require a permanent pacemaker implantation. This would be more significant in most of the developing world, where resources are scarce.